Molecular Detection and Evolutionary Insights of Contagious Ecthyma (Orf) Virus in Goat in Andhra Pradesh, India - Devi Bodlapati, Vimala; Gangaraju, Sireesha; Dwarakacherla, Neeraja; Narayana, Ramachandra; babu Gundampati, Ravi (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Contagious ecthyma or Orf is a zoonotic, transboundary disease affecting both domestic and wild ruminants. The present study investigated the incidence of severe Orf outbreaks in goats in Kurnool and Anantapur districts of Andhra Pradesh, a southern state of India during 2024. The presence of the Orf virus in the clinical samples was confirmed by PCR targeting the GM-CSF/IL-2 inhibitor (GIF) gene. Among the 11 samples tested, four skin scab samples yielded a positive result, showing a specific 408 bp PCR amplicon. Further testing using a capripox genus-specific PCR assay confirmed the absence of sheep pox and goat pox viruses in the samples. This is the first study on comprehensive genetic characterization of circulating ORFV strains in Andhra Pradesh. Phylogenetic analysis revealed two ORFV isolates (ATP 2833 and KRNL 4410) belong to distinct groups, sharing 97.46% nucleotide identity with each other. ATP 2833 isolate showed highest homology with Tamil Nadu field isolates and the TANUVAS P15 vaccine strain suggesting southern Indian ORFV circulation patterns. In contrast, KRNL 4410 strain demonstrated close phylogenetic proximity to the IVRI Mukteshwar P50 vaccine strain and Ludhiana 2006 strain, suggesting a possible association with vaccine-related lineages circulating in northern India. The divergence of both strains from the first-generation NZ2 isolate (1982) and the Japan (1985) isolate highlights significant evolutionary changes over time. These alterations are likely driven by regional transmission dynamics such as climate, host and breed characteristics. These results indicate the potential for regional variations in ORFV strains, which could have important implications for vaccine development and the optimization of disease control strategies.